Multidimensional applications of prussian blue-based nanoparticles in cancer immunotherapy - Jiayi Zhang; Fang Wang; Zhaogang Sun; Jun Ye; Hongqian Chu (Journal of Nanobiotechnology)
Abstract Immunotherapy holds notable progress in the treatment of cancer. However, the clinical therapeutic effect remains a significant challenge due to immune-related side effects, poor immunogenicity, and immunosuppressive microenvironment. Nanoparticles have emerged as a revolutionary tool to surmount these obstacles and amplify the potency of immunotherapeutic agents. Prussian blue nanoparticles (PBNPs) exhibit multi-dimensional immune function in cancer immunotherapy, including acting as a nanocarrier to deliver immunotherapeutic agents, as a photothermal agent to improve the efficacy of immunotherapy through photothermal therapy, as a nanozyme to regulate tumor microenvironment, and as an iron donor to induce immune events related to ferroptosis and tumor-associated macrophages polarization. This review focuses on the advances and applications of PBNPs in cancer immunotherapy. First, the biomedical functions of PBNPs are introduced. Then, based on the immune function of PBNPs, we systematically reviewed the multidimensional application of PBNPs in cancer immunotherapy. Finally, the challenges and future developments of PBNPs-based cancer immunotherapy are highlighted. Graphical abstract